Effect of compassion‐focused group therapy on psychological symptoms in mothers of attention‐deficit hyperactivity disorder children: A pilot study. Issue 2 (25th February 2019) - Navab, Mojgan; Dehghani, Akram; Salehi, Mehrdad
Abstract: Background: Evidence suggests that attention‐deficit/hyperactivity disorder (ADHD) may accentuate varying psychological symptoms in parents. Since mothers are the most likely individuals interacting with ADHD children, it is highly probable that they will be influenced the most. Objectives: This pilot study aimed to determine the effect of compassion‐focused group therapy on psychological symptoms of mothers of ADHD children. Methods: A pre‐test–post‐test control‐grouped, quasi‐experimental study was carried out on a sample of 20 mothers of children with ADHD who were referred to the Health Centers of Isfahan City in Spring 2017. Prior to the intervention, the mothers' psychological symptoms were recorded in both groups using the DASS‐21 questionnaire. Then, the mothers ( n = 10) in the treatment group underwent 8 weekly sessions of 90‐min, compassion‐focused therapy. Both groups were post‐tested 1 week after the intervention. Finally, the collected data were analysed in SPSS‐23. Results: The results of the study showed that, after the intervention, the mothers' psychological symptoms in the treatment group significantly decreased (pre‐test: 36.10 ± 7.96 vs. post‐test: 33.40 ± 4.28, p value < 0.05), while no significant change was observed in the control group. Depression and anxiety levels showed a significant decrease in the treatment group as compared to the control group ( p value < 0.05), while participants' stress levels remained the same in both groups ( p value > 0.05). Conclusion: The findings revealed that compassion‐focused therapy resulted in an increase in self‐compassion and inner calmness levels, and a decrease in the use of avoidance coping strategy on the one hand, and the need to regulate emotions and ruminations on the other hand, among the mothers of ADHD children, which subsequently led to a decrease in psychological symptoms.